Uso de mampostería modular en Costa Rica: ¿Es realmente un material cero residuos? - Cruz Zúñiga, Nidia (2022)
Masonry construction is the most used method for developing housing projects in Costa Rica. For several decades now, modular masonry systems have been gaining strength. According to their manufacturers, among the main benefits are not requiring formwork systems and the reduction of block waste to practically zero. Although the use of these systems is not yet widespread, according to research carried out, these systems are more used in large construction companies and mass construction, reaching 25% of housing projects in the country. The current investigation sought to quantify the construction waste generated in housing projects built with modular masonry and compare the results of the waste generation rate (kg/m2) with housing projects built with non-modular confined masonry (traditional method). It was possible to show how for some materials, the amount of waste does decrease (wood). However, in general, significantly lower waste generation rates are not achieved, nor is zero waste achieved in masonry blocks. It was also evidenced that there are many other variables involved in generating construction waste, in which labor and the type of contracting are the most influential.